Eugenics on the Periphery: Or Why a ‘Belarusian Eugenic Project’ Did Not Come True (1918–44) - Zamoiski, Andrei (Acta Poloniae Historica, 2016)
The interwar period was characterized by the active development of national eugenics projects in Europe. A number of factors contributed to the interest in eugenics and the desire to implement them: the making of new states and consolidation of nations in East Central Europe, the need to overcome the legacy of the Great War and deal with social problems (for example, venereal diseases and prostitution), and the development of scientific and international academic contacts. Belarusian debates on eugenics took place mostly on the periphery of the more developed discourses – those in Russia, Poland, and, later on, in Germany. The Russian scholars in the larger university centres contributed to the development of the Soviet eugenics project, which gained the support of the Soviet authorities. In the first decade of their rule, the Bolsheviks were not against debates on eugenics about how to improve the ‘nature of man’. The Soviet eugenics project, which focused on studying problems of heredity, genetics, and genealogy, was stopped when the authorities placed rigid ideological controls over science. In Soviet Belarus, no academic circle appeared that engaged in the debates on eugenics. The development of the eugenics movement in Poland was closely linked to the formation of the newly established Polish state. After the Great War, the Polish eugenics movement made attempts to integrate itself into the public life of the country. Polish medical doctors contributed to the development of the eugenics movement. During the Second World War, a group of Belarusian nationalists tried to formulate a basis for a Belarusian racial eugenics project, following the main ideas of Nazi ‘racial hygiene’.